Netpolitik: A New Political Transformer for Indonesia? - Bustanul Arifin; Amirah Ulfah (President University, 2018)
The development of Information and Communication Technologies (ICTs) has brought many fundamental changes in the political practices. One of the main essential aspects of ICTs is internet. This internet plays an important role in developing the information age. Therefore, the information age contributes to the way in which we effectively and efficiently create and consume the information. In this research, we focus to see the role of technology that drives to the practice of netpolitik by both the public and political actors in Indonesia. Netpolitik itself is the combination between internet and politic. Then, we analyze how netpolitik is influencing and changing the political situation in Indonesia during the recent time. Then, we put several aspects in order to see the effects driven by the netpolitik. Finally, we conclude the research by a finding stating that the netpolitik has done a political transformation in Indonesia and it becomes a core engine in determining the behaviour of political actor and audiences.Keywords: Internet, Netpolitik, Public, Political Actors, ICTs, Digital Era, Transformation, and Indonesia